Classical Ethical Values for Modern Challenges: Al-Ghazali’s Bidayatul Hidayah and Its Relevance to National Character Education - Ahmad Lutfi; Jaenullah Jaenullah; Muhammad Syaifullah (CV. Bimbingan Belajar Assyfa, 2026)
This research is motivated by the moral crisis among Indonesian youth, characterized by high rates of violence, bullying, and value degradation within educational environments. While moral education in Islam is central to forming a complete human being, its implementation faces significant contemporary challenges. This study aims to analyze the moral education values from Imam Al-Ghazali’s perspective in the book Bidayatul Hidayah and determine their relevance to national character education in Indonesia. The research employs a qualitative method with a library research approach, utilizing Bidayatul Hidayah as primary data and relevant literature as secondary sources, analyzed through descriptive-analytical techniques. The results indicate that Bidayatul Hidayah contains fundamental moral values covering relations with God (habl min Allah), oneself, and society (habl min al-nas), emphasizing the process of tazkiyatun nafs (soul purification) by integrating knowledge and practice. Furthermore, these values demonstrate strong conceptual, methodological, and socio-cultural relevance to Indonesia's national character education. The study concludes that Al-Ghazali’s moral values can serve as a practical and conceptual reinforcement for national character education, recommending their integration to foster students with noble character and spiritual maturity.